The Effect of Clustering Technique on Students’ Achievement in Writing Skill Recount Text at the Ninth grades Students of SMPN 5 Masbagik - Serlina Aini; M. Adib Nazri; Yulia Agustina; Hajriana Arfah (Jurnal Studi Guru dan Pembelajaran, 2025)
This research aims to know the effect of the Clustering Technique on students’ achievement in writing recount texts at the ninth grade of SMPN 5 Masbagik in the school year 2025–2026. The study applied a true experimental design with a pre-test and post-test control group. The sample consisted of 60 students selected through simple random sampling, with 30 students in the experimental group and 30 in the control group. The instrument used was a writing test assessed on content, organization, vocabulary, and language use, with proven validity and high reliability (Cronbach’s Alpha = 0.936). The experimental group was taught recount text writing using the clustering technique, while the control group received conventional instruction. Data were analyzed using descriptive statistics, normality and homogeneity tests, and an independent sample t-test. The results revealed that the experimental group's mean score improved from 56.33 (SD = 6.52) in the pre-test to 71.40 (SD = 7.38) in the post-test, while the control group's mean score increased from 49.87 (SD = 5.20) to 53.40 (SD = 5.78). The independent sample t-test indicated a significant difference between the post-test scores of the two groups (t = 10.513, p < 0.05), confirming that the clustering technique significantly enhanced students' writing achievement. Based on the data analysis, the researcher concluded that clustering is an effective pre-writing strategy to improve the ability to generate and organize ideas, leading to better recount text writing performance.